Kinetic modeling as a tool to understand the influence of cell culture process parameters on the glycation of monoclonal antibody biotherapeutics. (21st June 2019) - Agarwal, Nitin; Mason, Alison; Pradhan, Rahul; Kemper, Jan; Bosley, Allen; Serfiotis‐Mitsa, Dimitra; Wang, Jihong; Lindo, Viv; Ahuja, Sanjeev; Hatton, Diane; Savery, James; Miro‐Quesada, Guillermo
Abstract: Glycation, the nonenzymatic reaction between the reducing sugar glucose and the primary amine residues on amino acid side chains, commonly occurs in the cell culture supernatant during production of therapeutic monoclonal antibodies (mAbs). While glycation has the potential to impact efficacy and pharmacokinetic properties for mAbs, the most common undesirable impact of glycation is on the distribution of charged species, often a release specification for commercial processes. Existing empirical approaches are usually insufficient to rationalize the effects of cell line and process changes on glycation. To address this gap, we developed a kinetic model for estimating mAb glycation levels during the cell culture process. The rate constant for glycation, including temperature and pH dependence, was estimated by fitting the kinetic model to time‐course glycation data from bioreactors operated at different process settings that yielded a wide range of glycation values. The parameter values were further validated by independently estimating glycation rate constants using cell‐free incubation studies at various temperatures. The model was applied to another mAb, by re‐estimating the activation energy to account for effect of a glycation "hotspot". The model was further utilized to study the role of temperature shift as an approach to reduce glycation levels in the manufacturing process for mAb2. While a downshift in temperature resulted in lowering of glycation levels for mAb2, the model helped elucidate that this effect was caused due to contribution from changes in glucose consumption, mAb secretion and temperature, instead of a direct impact of temperature alone on the kinetic rate of glycation.